Infrastructure quality, cross-border connectivity, and trade costs - Elvira Kurmanalieva (Asian Development Bank Institute (ADBI), 2020)
Trade costs incorporate the cost of transportation along with tariffs, nontariff measures, insurance, distribution costs, infrastructure quality, and cross-border connectivity. The high costs of trade make the production process slow and costly, which forces international trade flows to concentrate on locations with better infrastructure quality and lower tariffs while abandoning the rest to the periphery. This is how hubs and spokes arise. This evolving process in international trade does not seem to favor geographically disadvantaged remote islands and landlocked countries that are desperately seeking to improve their access to global distribution networks. This paper uses a new approach to measure various indicators of cross-border connectivity by considering so-called "betweenness centrality," which, broadly interpreted, is the efficiency of networks' relationships. It then estimates the trade cost function as a function of cross-border connectivity, distance, and infrastructure quality.
Keywords: R12; R41; F14; 330; trade cost; infrastructure quality; cross-border connectivity; betweenness centrality